Caries severity in relation to oral health knowledge and behavior of third and fifth year dental students / University of Baghdad (A comparative study) - Nibal M Hoobi (College of Dentistry/ University of Baghdad, 2014)
Background: Tooth wear is one of the most common problems in the older dentate population which results from the interaction of three processes (attrition, abrasion and erosion) and it affects all societies, different age groups, and all cultures. This study was achieved to evaluate the prevalence and distribution of tooth wear among institutionalized residents in Baghdad city\ Iraq. Subjects and Methods: This survey was accomplished on four private and one governmental institution in Baghdad city. One-hundred twenty three (61 males, 62 females) aged 50-89 years were participated in this study. The diagnosis and recording of tooth wear were according to criteria of Smith and Knight. Results: The prevalence of tooth wear was 100% with a mean (30.79± 19.39) and median (28). The highest grade of tooth wear recorded was grade 2 (56.9%), followed by grade 3 (26%), grade 4 (17.1%). There was no statistically significant difference of total tooth wear among age groups (P>0.05), astatistically significantdifference was seen regarding the severity of tooth wear among different age groups; for grade 2 and grade 4 (P